Human rights, equality, and democratic renewal in Northern Ireland - Harvey, Colin J. (Hart, 2001)
Recent developments in Northern Ireland have been described as historic, with the Good Friday Agreement of 1998 ensuring a new form of constitutionalism. This text examines several key aspects of this complex picture.